Implementasi Kebijakan Sistem Zonasi pada Penerimaan Peserta Didik Baru di Sekolah Menegah Pertama Kabupaten Langkat - Candra Wijaya; Ahmad Fuadi; Syahrul Hasibuan (Universitas Negeri Medan, 2020)
To overcome the problem of education quality, the government issued a zoning system policy on New Student Admissions. This study aims to described the implementation of zoning system policies and constraints faced in implemented the new student admission zoning system policy at the junior high school level in Langkat District. This study used a qualitative approach with a case study method. The subjects of this study were the Middle School Curriculum Head, Middle School Curriculum Staff, Head of Elementary Education, Deputy Head of Student Affairs, Deputy Principal The technique of collecting data used observation, interviews, and documentation. The results of the study are as follows: (1) The implementation of the zoning system in the PPDB at the junior high school level in Langkat District has been carried out for two years aimed at equitable distribution of quality education in schools in the Langkat Regency, so far the implementation of the zoning system in Langkat has been effective because the potential of students begins to be evenly distributed in the Langkat Regency. (2) The constraints faced in the implementation of the zoning system are the lack of understanding of the zoning of the socialization of the zoning system because of the different backgrounds of parental education. Efforts are made to overcome these obstacles, namely to disseminate the zoning system early as clearly as possible.